Developmental changes in brain activation involved in the production of novel speech sounds in children. Issue 8 (2nd March 2014) - Hashizume, Hiroshi; Taki, Yasuyuki; Sassa, Yuko; Thyreau, Benjamin; Asano, Michiko; Asano, Kohei; Takeuchi, Hikaru; Nouchi, Rui; Kotozaki, Yuka; Jeong, Hyeonjeong; Sugiura, Motoaki; Kawashima, Ryuta
Abstract Older children are more successful at producing unfamiliar, non‐native speech sounds than younger children during the initial stages of learning. To reveal the neuronal underpinning of the age‐related increase in the accuracy of non‐native speech production, we examined the developmental changes in activation involved in the production of novel speech sounds using functional magnetic resonance imaging. Healthy right‐handed children (aged 6–18 years) were scanned while performing an overt repetition task and a perceptual task involving aurally presented non‐native and native syllables. Productions of non‐native speech sounds were recorded and evaluated by native speakers. The mouth regions in the bilateral primary sensorimotor areas were activated more significantly during the repetition task relative to the perceptual task. The hemodynamic response in the left inferior frontal gyrus pars opercularis (IFG pOp) specific to non‐native speech sound production (defined by prior hypothesis) increased with age. Additionally, the accuracy of non‐native speech sound production increased with age. These results provide the first evidence of developmental changes in the neural processes underlying the production of novel speech sounds. Our data further suggest that the recruitment of the left IFG pOp during the production of novel speech sounds was possibly enhanced due to the maturation of the neuronal circuits needed for speech motor planning. This, in turn, would lead to improvement in the ability to immediately imitate non‐native speech. Hum Brain Mapp 35:4079–4089, 2014. © 2014 Wiley Periodicals, Inc.